EVERY STEP MATTERS: REDUCING FALLS IN ONCOLOGY PATIENTS. - Stein, Charlene E.; Ferguson, Brooke; Delevett, Rachel; Huffman, Alexandra (Oncology Nursing Forum, 2026)
Significance & Background: Falls remain a significant safety concern for oncology patients, who are uniquely vulnerable due to cancer treatments, medication effects, and age-related comorbidities. Historically, fall prevention does not have a one-size fits all approach. At our organization's Cancer Center, an increase in patient falls was identified across outpatient clinics and common areas. Falls in oncology patients can delay treatment, extend length of stay, and diminish quality of life, underscoring the urgency of prevention strategies. Purpose: The purpose of this quality improvement initiative was to reduce falls with injury in outpatient settings while strengthening both staff and patient education. The project sought to ensure that all team members--including non-clinical staff such as valet attendants and guest services--were prepared to identify, prevent, and respond to fall risks. Patient-centered outcomes included improving awareness of personal risk factors and providing strategies for prevention both in clinic and at home. The team established a goal of zero falls with injury across all locations. Interventions: A multidisciplinary Falls Prevention Committee was formed to design and implement interventions. The team launched Falls Prevention Awareness Week, which introduced a mandatory education module assigned to more than 1,300 cancer center employees. Targeted training sessions were developed for valet and guest services staff, who serve as first contact for patients arriving on campus. Wheelchair assistance scripting was revised, and standardized fall risk screening questions are in development for use at check-in. Patients identified as high risk are flagged in the electronic medical record (EMR), with the designation persisting across outpatient, inpatient, and radiation oncology visits. Results: While full outcome data are pending as modules are completed this fiscal year, early findings suggest improved staff awareness and engagement. Patients have also expressed greater understanding of their fall risk, with many noting they had previously attributed unsteadiness to age rather than cancer treatment. These preliminary results suggest that the interventions address key gaps in awareness. Discussion: This initiative highlights the value of a proactive, multidisciplinary approach to falls prevention in the oncology setting. Future steps include developing a sustainable EMR solution for tracking fall risk status, monitoring falls more systematically, and integrating oncology-specific fall education at the start of treatment. By prioritizing education and standardization, the cancer center aims to transform falls prevention from a reactive to a proactive component of care.